Hemodynamic Changes in the Masseter and Superior Orbicularis Oris Muscles before and after Exercise Load: A Comparison between Young Adult Women and Middle-Aged to Old Adult Women - Keiko Okamoto; Chihiro Tanikawa; Kenji Takada (Hindawi Limited, 2022)
Background. The vascularity index (VI) is useful for measuring the hemodynamics on ultrasound imaging. However, there are no reports concerning the application of the VI to facial muscles. Objective. The aim of this study was (1) to establish a method of measuring the hemodynamics in facial muscles in a constant way and (2) to evaluate the hemodynamic changes in the masseter and superior orbicularis oris muscles (SOOMs) before and after exercise load in two subject groups of females of different ages. Methods. (1) The VI in the SOOM was calculated, and the test-retest reliability was assessed in seven healthy adults. (2) The VIs in the left-side masseter and SOOM were calculated in 3 sessions: before exercise loading (T0), immediately after loading (T1), and 5 minutes after T1 (T2) for the young adult group (YAG, n = 20; age range, 20-35 years) and the middle-aged to old group (MOG, n = 20; age range, 50-70 years). Tasks were gum chewing for the masseter muscle and lip sealing for the SOOM. The differences in the mean peak flows between two sessions were examined. Results. (1) Significant differences were not noted for the repeatedly measured average volumes of blood flow with good test-retest agreement (intraclass correlation coefficient = 0.81). (2) In both muscles of the YAG, there were a significant increase in T1 compared with T0 and a significant decrease in T2 compared with T1 (all p<0.05). In both muscles of the MOG, no significant differences were noted in either comparison. Conclusions. A method of measuring the hemodynamics in facial muscles was developed and showed good reliability. Changes in the blood flow after exercise load in these muscles may vary with age in women.